Formal, Legal, and Infrastructural Aspects of Competing – Survey Results from the Polish Road Freight Sector - Malgorzata KEDZIOR-LASKOWSKA (Communications of International Proceedings, 2020)
Polish road carriers constitute an essential part of the European transport market. They are responsible for approximately 10% of the cargo transport volume, also effectively competing with foreign carriers. The Polish road transport sector is characterised by a relatively high interference of the state (direct and indirect). This article attempts to assess the impact of formal, legal, and infrastructural determinants on the competitiveness of Polish road carriers. The research survey was conducted twice, in 2013 and 2019, which allowed for the comparative analysis and determination of the directions of changes. The sphere of regulations was described by 8 factors of legal and formal nature and infrastructural conditions. These factors were subjected to the respondents’ evaluation. The statistical analysis employed measures of location and variation. The changes in the influence of the studied determinants were established with the Mann–Whitney U test. The research results prove the increased importance of formal, legal, and infrastructural factors in shaping the competitiveness of road carriers. Furthermore, they show a greater heterogeneity in a group of micro-enterprises than in a group of enterprises employing more than 9 persons.
Keywords: Transport; Competitiveness; Poland; Freight.